Bagi Hasil Tambang Emas dalam Perspektif Ekonomi Islam (Studi Pada Tambang Emas Gogorea Kec.Waeapo. Kab.Buru). - Hayati Hehamahua (UPT Penerbitan Universitas Jember, 2020)
The Gogorea Village Gold Mine is located on the eucalyptus area of the village of Gogorea, which is the owner of the heir of King Liliyali. Community gold mining that occurs in the Mount Botak gold mining area is a lesson for the owner of the Gogorea gold mine to make local rules or laws in managing gold mines. This study aims to determine the profit sharing system of gold mining management between miners and gold mining area owners from an Islamic economic perspective with a qualitative approach. Humans only borrow and use natural resources that Allah has provided, and have no right to control them absolutely. In an Islamic perspective, muamalah transactions take place honestly and transparently in order to avoid conflict and mafsadah (damage). With an Islamic economic approach, the research findings are (a). Initially, the Gogorea gold mining area was an eucalyptus land owned by the heir of King Liliyali so that bargaining power belongs to the heir's family, (b). The internal regulations that have been implemented have been able to reduce conflicts in the Gogorea gold mining area. (c). The existence of this local law is able to guarantee harmony and fraternal relations between miners and mining area owners.